PD-L1 upregulation in myeloma cells by panobinostat in combination with interferon-γ - Iwasa, Masami (Oncotarget, 2019)
Immunotherapy is revolutionizing the treatment paradigm for multiple myeloma (MM). Interferon (IFN)-γ is essential for immune responses, whereas immune checkpoint molecules, such as programmed cell death-1 ligand-1 (PD-L1), mitigate the beneficial anti-tumor immune responses. As HDAC inhibitors alter the immunogenicity and anti-tumor immune responses, we here explored the regulation of PD-L1 expression in MM cells by the clinically available HDAC inhibitor panobinostat in the presence of IFN-γ. IFN-γ activated the STAT1-IRF1 pathway to upregulate PD-L1 expression in MM cells, and panobinostat was able to upregulate their PD-L1 expression without activating the STAT1-IRF1 pathway. Of note, panobinostat enhanced IFN-γR1 expression, which substantially increased the total and phosphorylated levels of STAT1 protein but reduced IRF1 protein levels through proteasomal degradation in the presence of IFN-γ. Panobinostat further enhanced the IFN-γ-mediated durable STAT1 activation in MM cells; STAT1 gene silencing abolished the PD-L1 upregulation by panobinostat and IFN-γ in combination, indicating a critical role for STAT1. These results suggest that panobinostat enhances PD-L1 expression by facilitating the IFN-γ-STAT1 pathway in a ligand-dependent manner in MM cells with ambient IFN-γ. PD-L1 upregulation should be taken into account when combining immunotherapies with panobinostat.